The Routledge handbook of metaphor and language (Routledge, 2017)
The Routledge Handbook of Metaphor and Language provides a comprehensive overview of state-of-the-art interdisciplinary research on metaphor and language. Featuring 35 chapters written by leading scholars from around the world, the volume takes a broad view of the field of metaphor and language, and brings together diverse and distinct theoretical and applied perspectives to cover six key areas: